The heat stability of milk protein-stabilized oil-in-water emulsions: A review. (March 2017) - Liang, Yichao; Matia-Merino, Lara; Gillies, Graeme; Patel, Hasmukh; Ye, Aiqian; Golding, Matt
Abstract: The knowledge on the factors affecting the heat-induced physicochemical changes of milk proteins and milk protein stabilized oil-in-water emulsions has been advanced for the last decade. Most of the studies have emphasized on the understanding of how milk-protein-stabilized droplets and the non-adsorbed proteins determine the physicochemical and rheological properties of protein-concentrated dairy colloids. The physical stability of concentrated protein-stabilized emulsions (i.e., against creaming or phase separation/gelation after heat treatment) can be modulated by carefully controlling the colloidal properties of the protein-stabilized droplets and the non-adsorbed proteins in the aqueous phase. This article focusses on the review of the physical stability of concentrated milk protein-stabilized oil-in-water emulsions as influenced by physicochemical factors, interparticle interactions (i.e., protein–protein, and droplet–droplet interactions) and processing conditions. Emphasis has been given to the recent advances in the formation, structure and physical stability of oil-in-water emulsions prepared with all types of milk proteins, reviewing in particular the impact of pre- and post-homogenization heat treatments. In addition, the importance of common components found in the continuous phase of heat-treated nutritional emulsions that can promote aggregation (polymers, sugars, minerals) will be highlighted. Finally, the routes of manipulating the steric stabilization of these emulsions to control heat-induced aggregation—through protein–surfactant, protein–protein, protein–polysaccharide interactions and through the incorporation of protein based colloidal particles—are reviewed. Graphical abstract: Highlights: Emulsion heat stability is dependent on protein-stabilized droplets and non-adsorbed proteins interactions. Recent advances on the impact of pre- and post-homogenization heat treatments are reviewed. The impact of polymers, sugars and minerals in the continuous phase of heat-treated nutritional emulsions is reviewed. Advances on manipulating the steric stabilization of the emulsions to control heat-induced aggregation are highlighted.